The third way of worship in M. Luther: A protestant perspective about the place of small home groups in the Christian Church - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2018)
The purpose of this study is to contribute to the historical-ecclesiastical, but also to the biblical-theological, theological-practical foundation of what we call “small groups in houses,” “church houses,” “home cells,” “church in cells “, among the various nomenclatures used today. More specifically, the approach is to devote itself to understanding the vision of the Reformer Martin Luther on the so-called “third form of worship,” found in the Preface to his German Mass and Order of Worship of 1526 in its historical, theological, and current relevance. Luther’s text, considered paradigmatic in relation to the subject in the history of the research, will be interpreted within the context of the Preface to the German Mass and the whole of Luther’s understanding of the place and function of the cults in the Christian church according to their various emphases, which will be explored in detail throughout the interpretation. The final will present a brief synthesis and reflection on the current relevance of the Reformer’s vision. The research is not so much intended to present new facts, but rather to rescue and summarize important results of international research, and socialize them in Portuguese, to Brazilian researchers.